Betacellulin-Induced α-Cell Proliferation Is Mediated by ErbB3 and ErbB4, and May Contribute to β-Cell Regeneration - Lee, Young-Sun; Song, Gyun Jee; Jun, Hee-Sook (Frontiers in Cell and Developmental Biology, 2021)
Betacellulin (BTC), an epidermal growth factor family, is known to promote β-cell regeneration. Recently, pancreatic α-cells have been highlighted as a source of new β-cells. We investigated the effect of BTC on α-cells. Insulin+glucagon+ double stained bihormonal cell levels and pancreatic and duodenal homeobox-1 expression were increased in mice treated with recombinant adenovirus-expressing BTC (rAd-BTC) and β-cell-ablated islet cells treated with BTC. In the islets of rAd-BTC-treated mice, both BrdU+glucagon+ and BrdU+insulin+ cell levels were significantly increased, with BrdU+glucagon+ cells showing the greater increase. Treatment of αTC1-9 cells with BTC significantly increased proliferation and cyclin D2 expression. BTC induced phosphorylation of ErbB receptors in αTC1-9 cells. The proliferative effect of BTC was mediated by ErbB-3 or ErbB-4 receptor kinase. BTC increased phosphorylation of ERK1/2, AKT, and mTOR and PC1/3 expression and GLP-1 production in α-cells, but BTC-induced proliferation was not changed by the GLP-1 receptor antagonist, exendin-9. We suggest that BTC has a direct role in α-cell proliferation via interaction with ErbB-3 and ErbB-4 receptors, and these increased α-cells might be a source of new β-cells.